Lower limb strength and training experience in elite and sub-elite female footballers - Fallon Verbruggen, F.; Hank, M.; Mirátský, P.; Malý, T.; Zahálka, F. (Isokinetics and Exercise Science, 2024)
BACKGROUND: Strength differences between performance levels remain unclear in female football. Furthermore, the relationship between fulltime training and strength has been unexplored despite increased professionalisation in the sport.